Critical Analysis of Shalih Ibn Fauzan’s Tauhid Materials on Three Modern Islamic Boarding Schools in Banten - Sunandar, Dadan; Syafei, Zakaria; Muhajir, Muhajir (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This article aims to explore Puritan ideology in modern Islamic boarding schools by using monotheism material by Shalih ibn Fauzan as teaching material and educational model. Analytical descriptive qualitative research method with research objects at three Khalafi/modern Islamic boarding schools, including the Darunna'im Modern Islamic Boarding School, LaTansa modern cottage, and Darel Azhar's modern cottage. Through document collection techniques, observation, and interviews. The analysis techniques include data reduction, data display, inference, and verification. The research results show that there is a Puritan ideology in Islamic boarding schools. There are at least three typologies of purification: (1) Islamic boarding schools in the Radical Puritan typology, (2) Islamic boarding schools with a modernist Puritan typology, and (3) adherents of accommodationism. Shalih ibn Fauzan's opinion regarding other assumptions regarding the Islamic boarding school typology in the Radical Puritan typology can be seen from the way Padang responds to several religious issues that exist in society. Modernist Puritans can be used as a reference in responding to developments and phenomena that occur in non-rigid societies. Meanwhile, the accommodationist Puritan group is more adaptable and adaptable in responding to various religious traditions. Tauhid education must be comprehensive, including tauhîd rubûbiyah, ulûhiyah, and asmâ' and shifât, because it will form a Muslim character who loves the science of Kauni as has been practiced in the three Islamic boarding schools.